2015
DOI: 10.1021/acs.inorgchem.5b02349
|View full text |Cite
|
Sign up to set email alerts
|

Actinide(IV) Deposits on Bone: Potential Role of the Osteopontin–Thorium Complex

Abstract: In case of a nuclear event, contamination (broad or limited) of the population or of specific workers might occur. In such a senario, the fate of actinide contaminants may be of first concern, in particular with regard to human target organs like the skeleton. To improve our understanding of the toxicological processes that might take place, a mechanistic approach is necessary. For instance, ∼50% of Pu(IV) is known from biokinetic data to accumulate in bone, but the underlining mechanisms are almost unknown. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…It has been reported that the Runx2 gene activates the transcription and expression of OCN, OPN, bone sialoprotein and type I collagen by binding to the cis-acting elements of osteoblasts (50). OPN serves an important role in the mineralisation and absorption of bone matrix (51). OCN is an important component of the extracellular matrix and is regarded as a specific marker of the bone turnover process (52); when OCN is in an inactive state, it directly affects the formation, absorption and mineralisation of bone (53).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the Runx2 gene activates the transcription and expression of OCN, OPN, bone sialoprotein and type I collagen by binding to the cis-acting elements of osteoblasts (50). OPN serves an important role in the mineralisation and absorption of bone matrix (51). OCN is an important component of the extracellular matrix and is regarded as a specific marker of the bone turnover process (52); when OCN is in an inactive state, it directly affects the formation, absorption and mineralisation of bone (53).…”
Section: Discussionmentioning
confidence: 99%
“…The binding of metals to a protein can be monitored by several techniques, such as fluorescence spectroscopy, isothermal titration calorimetry (ITC), time-resolved laser spectroscopy (TRLS), capillary electrophoresis coupled with an inductively coupled plasma mass spectrometer (CE-ICP-MS), and a binding constant expressed as K d , K, or pK d can be determined. [17][18][19][20] This overall constant reflects the protein's affinity for the metal whatever the number of metal binding sites. A small K d or a high K means that the protein's affinity for the metal is strong.…”
Section:  Introductionmentioning
confidence: 99%
“…On the other hand, there is no visible change associated with the symmetric stretching frequency of the carboxylate groups at about 1402 cm À1 .D enticity of the carboxylicg roups with the oxocation has been reportedly found, withadifference betweena symmetrica nd symmetric stretching frequencies. [7] Thisisn ot visible here. In addition, we could not find ar eproducible methodo fc reatingt he difference absorption spectra, owing to the strong amide II band.…”
Section: àmentioning
confidence: 79%
“…On the other hand, there is no visible change associated with the symmetric stretching frequency of the carboxylate groups at about 1402 cm −1 . Denticity of the carboxylic groups with the oxocation has been reportedly found, with a difference between asymmetric and symmetric stretching frequencies . This is not visible here.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation